Методика оценки эффективности теплогенератора пиролизного типа в нестационарном режиме эксплуатации - Семеней, А. П.; Братута, Эдуард Георгиевич (НТУ "ХПИ", 2010)
The method of the experiment and experiment data treatment during investigation of pirolize type steam generator under non-stationary working regimes have been presented
Keywords: биомасса; топливо; испытание аппарата; продукты сгорания